Genetic diversity and population structure of cacao (Theobroma cacao L.) germplasm from Sierra Leone and Togo based on KASP- SNP genotyping - Bhattacharjee, Ranjana; Luseni, M.M.; Ametefe, K.; Agre, P.A.; Kumar, P.L.; Grenville-Briggs, L.J. (Research Square Platform LLC, 2024)
Background Cacao (Theobroma cacao L.) is a tropical tree species belonging to Malvaceae family and originated in the lowland rainforests of the Amazon. It is one of the major agricultural commodities contributing towards the GDP (gross domestic product) of West African countries contributing about 70% of world’s production.